Muslim Food Consumer Protection Through The Regulation Of Halal Labels In Indonesia - Yuyut Prayuti (Fakultas Hukum Universitas Mataram, 2020)
The label is a tool to convey information about the products listed on the packaging. In addition to providing information about the product name, the label also provides information on the list of ingredients contained in the product, net weight, durability, value or usefulness of the product as well as information about halal. Objection is the main parameter in the product selection process. This provision makes limitations on food products to enter the Muslim market. This study aims to find out how is the form of legal protection for Muslim food consumers according to the applicable law in Indonesia and Muslim food consumer legal remedies if they feel disadvantaged due to violations of the halal label rules in Indonesia. This research is a Normative Law research through library research. Meanwhile, the normative juridical approach is used. Methods of approach through legislation (Statute Approach) and data sources through the technique of documentation and data analysis through qualitative descriptive. This article concludes that the form of legal protection for Muslim consumers was regulated through the Consumer Protection Act (UUPK) and other laws. Legal efforts by consumers through dispute resolution outside the court and within the court and through the Consumer Dispute Resolution Agency (BPSK).